2020
DOI: 10.2147/ott.s227171
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Research Progress on the Prognostic Value of the Common Hematological Parameters in Peripheral Venous Blood in Breast Cancer</p>

Abstract: Breast carcinoma is one of the most malignant tumors, severely influencing the physical and mental health of people. The latest epidemiological and clinical studies have found that breast tumor and inflammation are determinate relationships with each other. Inflammation is an essential component of the tumor microenvironment, and the change of inflammatory cells might influence tumor progression, such as neoplastic cell proliferation, migration, invasion, the collapse of antitumor immunity, metastasis and so f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 62 publications
(64 reference statements)
3
47
0
Order By: Relevance
“…The mean total leukocyte count did not show any significant correlation with the control group but as the disease progressed from stage 1 to stage 4, the count decreased. The total leukocyte count is greatly affected by increase or decrease of neutrophils, eosinophils, lymphocytes, monocytes and basophils 11 . In the present study, the absolute neutrophil count did not show any significant correlation with the control group nor also with staging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean total leukocyte count did not show any significant correlation with the control group but as the disease progressed from stage 1 to stage 4, the count decreased. The total leukocyte count is greatly affected by increase or decrease of neutrophils, eosinophils, lymphocytes, monocytes and basophils 11 . In the present study, the absolute neutrophil count did not show any significant correlation with the control group nor also with staging.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR ratio was found to be higher in patients with axillary lymph node metastasis. Many studies have shown that a pre-operative increase in the NLR ratio suggests poor prognosis of the breast cancer patients; it can be used as an independent prognostic factor in breast carcinoma 11,16 . The process for elevated NLR is explained by relative increase in the neutrophil count and relative decrease in the lymphocyte count, causing the breakdown of balance in the tumour microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 As indicators of systematic inflammation status, neutrophil and monocyte were reported to have participated in tumor cell proliferation and migration, tumor progression and metastasis. 60 However, lymphocyte plays a key role in anti-tumor reaction, and lymphocyte cell counts reflect immune response status. Therefore, the levels of NLR, PLR and MLR could indicate the severity of aggressive Notes: Confidential Interval.…”
Section: Figurementioning
confidence: 99%
“…They are cost effective and can be easily examined in less complex laboratories that do not have access to sophisticated technology for demonstration of more reliable cancer markers (14). Studies indicate hematological parameters as important investigations that are useful prognostic factors for evaluating the accuracy of risk strati cation in breast cancer patients (15,16). For example, a study done in south western Nigeria showed that HB, PCV, RBC and WBC were signi cantly lower in patients compared to controls (16).…”
Section: Hematological Pro Le and Breast Cancermentioning
confidence: 99%